Advances in Pharma Business Management and Research Volume 1 - Schweizer, Lars; Dingermann, Theodor; Russe, Otto Quintus; Jansen, Christian (Springer Nature, 2020)
This open access book presents a unique collection of practical examples from the field of pharma business management and research. It covers a wide range of topics such as: 'Brexit and its Impact on pharmaceutical Law - Implications for Global Pharma Companies', 'Implementation of Measures and Sustainable Actions to Improve Employee's Engagement', 'Global Medical Clinical and Regulatory Affairs (GMCRA)', and 'A Quality Management System for R&D Project and Portfolio Management in a Pharmaceutical Company'. The chapters are summaries of master's theses by "high potential" Pharma MBA students from the Goethe Business School, Frankfurt/Main, Germany, with 8-10 years of work experience and are based on scientific know-how and real-world experience. The authors applied their interdisciplinary knowledge gained in 22 months of studies in the MBA program to selected practical themes drawn from their daily business.